2011
DOI: 10.1007/s11250-011-9948-4
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors associated with bovine viral diarrhea virus (BVDV) infection in non-vaccinated dairy and dual purpose cattle herds in Ecuador

Abstract: A cross-sectional study was carried out to determine the seroprevalence and risk factors associated with Bovine viral diarrhea virus (BVDV) infection in non-vaccinated dairy and dual-purpose cattle herds from Ecuador. A total of 2,367 serum samples from 346 herds were collected from June 2008 through February 2009. A questionnaire, which included variables related to cattle, health, management measures, and the environment, was filled out in each herd. A commercial indirect enzyme-linked immunosorbent assay te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 18 publications
5
18
1
1
Order By: Relevance
“…Acquiring animals without checking their BVDV infection status is an important risk factor for BVDV infection in cattle herds. This is directly related to introducing PI animals that can carry the infection or new viral strains into the herds [38][39][40][41]. In 3 of the outbreaks reported here (outbreaks 3-5), the anamnestic information revealed that cattle from different origins were introduced and mixed into the herds without prior BVDV testing, which possibly contributed to disseminating and spreading infection and disease between farms.…”
Section: Discussionmentioning
confidence: 83%
“…Acquiring animals without checking their BVDV infection status is an important risk factor for BVDV infection in cattle herds. This is directly related to introducing PI animals that can carry the infection or new viral strains into the herds [38][39][40][41]. In 3 of the outbreaks reported here (outbreaks 3-5), the anamnestic information revealed that cattle from different origins were introduced and mixed into the herds without prior BVDV testing, which possibly contributed to disseminating and spreading infection and disease between farms.…”
Section: Discussionmentioning
confidence: 83%
“…Knowledge of herd management and environmental factors which enhance the risk of BVDV infection would improve the ability to control and prevent the transmission, reducing the detrimental impacts of BVDV infection on herd health and productivity (Saa et al 2012). Although the disease is under control or has even been eliminated in some European countries (Presi et al 2011), in developing countries (most of them located in tropical and subtropical areas) it is a primary source of economic losses due to a lack of preventive measures, such as vaccination and a poor knowledge of the true prevalence and the factors that determine it (Saa et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although the disease is under control or has even been eliminated in some European countries (Presi et al 2011), in developing countries (most of them located in tropical and subtropical areas) it is a primary source of economic losses due to a lack of preventive measures, such as vaccination and a poor knowledge of the true prevalence and the factors that determine it (Saa et al 2012). In China, vaccination and knowledge of the true prevalence and the factors are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Some European studies report several risk factors associated to infection with BoHV-1 such as animal age, vaccination status, herd size, production system (dairy or beef), season and introduction of animals to the farm (Boelaert et al, 2005;González-Garcia et al, 2009). Several reports associated risk factor to BVDV infection such as density of cattle farms, altitude, more than six calves aged ≤ 12 months, animal purchasing and presence of veterinary assistance (Saa et al, 2012;Fernandes et al, 2016). Therefore, information on the epidemiology of BoHV-1 and BVDV is important to establish if tailored prevention and control programs are required for specific regions.…”
Section: Introductionmentioning
confidence: 99%